2005
DOI: 10.1111/j.1471-4159.2005.03257.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity and behavioral deficits associated with Septin 5 accumulation in dopaminergic neurons

Abstract: Septin 5, a parkin substrate, is a vesicle-and membraneassociated protein that plays a significant role in inhibiting exocytosis. The regulatory function of Septin 5 in dopaminergic (DAergic) neurons of substantia nigra (SN), maintained at relatively low levels, has not yet been delineated. As loss of function mutations of parkin are the principal cause of a familial Parkinson's disease, a prevailing hypothesis is that the loss of parkin activity results in accumulation of Septin 5 which confers neuron-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 56 publications
4
52
0
Order By: Relevance
“…27,28 Interestingly, a neuron defect has been difficult to document in septin-5 Ϫ/Ϫ mice, but platelets lacking the protein demonstrate enhanced aggregation and release stored granule products in response to stimuli that are under the threshold for normal platelets. 15 Septin-5 has been localized to membrane areas surrounding platelet ␣-granules and binds syntaxin 4 to prevent rather than promote secretion.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Interestingly, a neuron defect has been difficult to document in septin-5 Ϫ/Ϫ mice, but platelets lacking the protein demonstrate enhanced aggregation and release stored granule products in response to stimuli that are under the threshold for normal platelets. 15 Septin-5 has been localized to membrane areas surrounding platelet ␣-granules and binds syntaxin 4 to prevent rather than promote secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, septin-dependent recruitment of a class of kinases to the bud neck region is a checkpoint for cell cycle progression. It has been demonstrated that septins can produce neuronal toxicity and motor behavioral dysfunction in dopaminergic neurons (Son et al 2005). They may also contribute to neoplasia by enhancing membrane dynamics (Polo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated midbrain sections (dissected as described in the study by Son and colleagues 26 ) were transferred to ice-cold Hank's Balanced Salt Solution (HBSS; Life Technologies), supplemented with 500 units of penicillin and 500 µg of streptomycin directly after isolation. Midbrains were then washed twice with 12 mL of HBSS and trypsinized in 4 mL of HBSS with 0.5% trypsin.…”
Section: Cell Culturementioning
confidence: 99%